The relationship between service quality towards customer satisfaction at Parkson Grand Mahkota Parade / Siti Radhiah Ismail - Ismail, Siti Radhiah (2014)
In the present retail outlet scenario, service quality is a vital competitive policy to keep customer support and build great base. Retail outlets nowadays are trying to win customer satisfaction by providing enhanced quality services. This research paper attempts to identify the relationship between service quality towards customer satisfaction at Parkson Grand Mahkota Parade. To achieve the objective, the researcher collected primary data and secondary data. The researcher used descriptive analysis and SPSS version 20 tools. A total of 50 surveys were administrated to customers who were shopping at Parkson Grand Mahkota Parade. The customers were selected using purposive sampling and simple random technique. The result shows that dimensions of service quality such as tangible, reliability, responsiveness, assurance and empathy significantly predict customer satisfaction. Specifically, among the dimensions of retail service quality, the most significant predictor of customer satisfaction is tangible. This research paper implies that Parkson Grand Mahkota Parade should also come forward and try their best to present better retail service quality to win back their customers’ satisfaction. The research findings shows that retail service quality at Parkson Grand Mahkota Parade are generally good. So that, it can be concluded that the relationship between service quality towards customers’ satisfaction were exists. It is recommended that employee motivation and employee training should be increased to improve retail service quality and it will be increased the customer satisfaction also.